Molecular characterization of vulnibactin biosynthesis in Vibrio vulnificus indicates the existence of an alternative siderophore - Tan, Wenzhi; Verma, Vivek; Jeong, Kwangjoon; Kim, Soo Y.; Jung, Che-Hun; Lee, Shee E.; Rhee, Joon H. (Frontiers in Microbiology, 2014)
Vibrio vulnificus is a halophilic estuarine bacterium that causes fatal septicemia and necrotizing wound infections in humans. Virulent V. vulnificus isolates produce a catechol siderophore called vulnibactin, made up of one residue of 2, 3-dihydroxybenzoic acid (2, 3-DHBA) and two residues of salicylic acid (SA). Vulnibactin biosynthetic genes (VV2_0828 to VV2_0844) are clustered at one locus of chromosome 2, expression of which is significantly up-regulated in vivo. In the present study, we decipher the biosynthetic network of vulnibactin, focusing specifically on genes around SA and 2, 3-DHBA biosynthetic steps. Deletion mutant of isochorismate pyruvate lyase (VV2_0839) or 2,3-dihydroxybenzoate-2,3-dehydrogenase (VV2_0834) showed retarded growth under iron-limited conditions though the latter showed more significant growth defect than the former, suggesting a dominant role of 2, 3-DHBA in the vulnibactin biosynthesis. A double deletion mutant of VV2_0839 and VV2_0834 manifested additional growth defect under iron limitation. Though the growth defect of respective single deletion mutants could be restored by exogenous SA or 2, 3-DHBA, only 2, 3-DHBA could rescue the double mutant when supplied alone. However, double mutant could be rescued with SA only when hydrogen peroxide was supplied exogenously, suggesting a chemical conversion of SA to 2, 3-DHBA. Assembly of two SA and one 2, 3-DHBA into vulnibactin was mediated by two AMP ligase genes (VV2_0836 and VV2_0840). VV2_0836 deletion mutant showed more significant growth defect under iron limitation, suggesting its dominant function. In conclusion, using molecular genetic analytical tools, we confirm that vulnibactin is assembled of both 2, 3-DHBA and SA. However, conversion of SA to 2, 3-DHBA in presence of hydrogen peroxide and growth profile of AMP ligase mutants suggest a plausible existence of yet unidentified alternative siderophore that may be composed solely of 2, 3-DHBA.